(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2016)
The emergence and spread of antibiotic resistance in microorganisms have rendered the management of infectious diseases difficult. Extended-Spectrum 3-Lactamases (ESBLs) producing organisms are increasing in number and causing more severe infections because of their continuous mutation and multidrug resistance property which make its treatment difficult. The present study was undertaken to detect the prevalence of the ESBLs producing bacteria in patients attending Chittagong Medical College Hospital, so as to provide a guideline in treating them & prevent unnecessary use of antibiotics. All the isolates were identified by standard procedure & isolated gram-negative bacteria initially screened by Minimum Inhibitory Concentration (MIC) ESBLs breakpoints. Then confirmed by Phenotypic Confirmatory Test (PCT). In the present study, 176(74.89%) bacterial strains were isolated from 235 samples of wound swab, pus and urine. Among the isolates, 150(85.23%) were gram-negative and 26(14.77%) were gram-positive bacteria. Isolated gram-negative bacteria were screened for suspected ESBLs producers where 142(94.67%) were found suspected ESBLs producers, of which 89(62.68%) confirmed as JCMCTA 2015 ; 26 (2) : 23 - 28